2004
DOI: 10.1590/s0041-87812004000200001
|View full text |Cite
|
Sign up to set email alerts
|

Surgery information reduces anxiety in the pre-operative period

Abstract: PURPOSE:Patients preparing to undergo surgery should not suffer needless anxiety. This study aimed to evaluate anxiety levels on the day before surgery as related to the information known by the patient regarding the diagnosis, surgical procedure, or anesthesia.METHOD: Patients reported their knowledge of diagnosis, surgery, and anesthesia. The Spielberger State-Trait Anxiety Inventory (STAI) was used to measure patient anxiety levels.RESULTS: One hundred and forty-nine patients were selected, and 82 females a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
80
2
20

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(114 citation statements)
references
References 14 publications
10
80
2
20
Order By: Relevance
“…Differently of our findings, Kiyohara et al [27] found no significant difference in anxiety levels between female and male. According to Gallagher and McKinley [31], information provided at the time before surgery to reduce anxiety, especially in women.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Differently of our findings, Kiyohara et al [27] found no significant difference in anxiety levels between female and male. According to Gallagher and McKinley [31], information provided at the time before surgery to reduce anxiety, especially in women.…”
Section: Discussioncontrasting
confidence: 99%
“…Corroborating the findings of this study presented herein, lower levels of anxiety were noted in those patients who had knowledge about the surgical procedure, as described by Kiyohara et al [27]. However, Bergmann et al [5] and Schuldham et al [28] found no significant difference in scores between patients guided or not on the same disorder before the surgery.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Come riportato da Kiyohara et al 28, una visita preoperatoria effettuata da un anestesista è la megliore educazione per il paziente e può ridurre significativamente l'ansia nei pazienti. Il miglioramento delle procedure chirurgiche e la dimissione precoce dei i pazienti significa che l'assistenza infermieristica oggi si concentra più sull'assistenza psicologica e di gestione dell'ansia, che sono diventati pietre miliari della assistenza infermieristica in chirurgia29.…”
Section: Nel 2006 Sawangarom In "Effect Of Preoperative Phone Call Ounclassified
“…Lack of adequate and timely information to patients during the pre-anesthetic consultation increases patient anxiety. Study done by Kiyohara et al found that patients receiving better preanesthetic information during the visit with the anesthesiologist showed reduced rates of anxiety [10]. The day of admission can also be a very stressful, as patients have to cope with both the stress of hospitalization and the anxiety about the impending surgery.…”
Section: Factors Related To Perioperative Anxietymentioning
confidence: 99%